Global administrative law and EU administrative law relationships, legal issues and comparison - Chiti, Edoardo; Mattarella, Bernardo Giorgio; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book seeks to enrich and refine global administrative law and EU administrative law analytical tools by examining their manifold relations. Its aim is to begin to explore the complex reality of the interactions between EU administrative law and global administrative law, to provide a preliminary map of such legal and institutional reality, and to review it. The book is the first attempt to analyze a dense area of new legal issues. The first part of the book contains core elements of a general theory of the relationships between global and EU administrative law: comparative inquiries, exchanges of legal principles, and developing linkages. The second part is devoted to special regulatory regimes, in which global and European law coexist, though not always peacefully. Several sectors are considered: cultural heritage, medicines, climate change, antitrust, accounting and auditing, banking supervision, and public procurement.
1. Introduction: the relationships between global administrative law and EU administrative law / Edoardo Chiti and Bernardo Giorgio Mattarella -- 2. EU and global administrative organizations / Edoardo Chiti -- 3. EU and global judicial systems / Barbara Marchetti -- 4. The influence of European and global administrative law on national administrative acts / Bernardo Giorgio Mattarella -- 5. The genesis and structure of general principles of global public law / Giacinto della Cananea -- 6. Administrative law beyond the State: participation at the intersection of legal systems / Joana Mendes -- 7. EU law, global law and the right to good administration / Juli Ponce Solé -- 8. "Interlocutory coalitions" and administrative convergence / Gianluca Sgueo -- 9. The impact of EU law and globalization on consular assistance and diplomatic protection / Stefano Battini -- 10. Public procurement and secondary policies in EU and global administrative law / Simona Morettini -- 11. The protection of cultural heritage between the EU legal order and global legal space / Carmen Vitale -- 12. The relationships between EU and global antitrust regulation / Elisabetta Lanza -- 13. The regulation of pharmaceuticals beyond the State: EU and global administrative systems / Alessandro Spina -- 14. EU and global private regulatory regimes: the accounting and auditing sectors / Maurizia De Bellis -- 15. The WTO and the EU: exploring the relationship between public procurement regulatory systems / Hilde Caroli Casavola -- 16. Basel-Brussels one way? The EU in the legalization process of Basel soft law / Enrico Leonardo Camilli -- 17. The review of compliance with the Aarhus Convention of the European Union / Rui Lanceiro -- 18. Private implementation of global and EU administrative law: the case of certification in the climate change regime / Georgios Dimitropoulos.
Electronic reproduction.
Keywords: Administrative law; Administrative law -- European Union countries; Electronic books